Scientology [soundrecording] : a new slant on life - Hubbard, L. Ron [ (La Fayette Ron)] , 1911-1986; Chase, Harry (Golden Era Productions, 2007)
Presents a selection of L. Ron Hubbard's discoveries, with each one providing a broad overview of Scientology applied to a specific aspect of human existence